Relevansi Mata Kuliah Ekonomi Moneter di Universitas Muhammadiyah Palangkaraya dengan Kurikulum SMA Bidang Studi Ekonomi - Iin Nurbudiyani (Pedagogik: Jurnal Pendidikan, 2014)
This study aims to find out how far the suitability between the subjects of Monetary Economics at the Muhammadiyah University of Palangkaraya and the Year High School Curriculum includes material, the number of face-to-face hours available. In this study the author using an exploratory type of research, while collecting the required data using the documentation method and the interview method. The research subjects were Muhammadiyah Palangkaraya University and High School Economics Subject Teacher Muhammadiyah I Kota Palangkaraya. While the object is the Syllabus of Monetary Economics Courses and Teachers in the Field of Economic Studies. The results of the study showed: (1) the material in Monetary Economics at the FKIP Muhammadiyah University in Palangkaraya presented 60% by the provisions of the High School Curriculum in the field of Economics. If we look at the competencies in the course of Monetary Economics with three topics, there are 15 sub-topics. Whereas in the curriculum with 3 subjects there are 18 sub-topics in the same curriculum with the sub-subjects in the course of Monetary Economics there are 9 sub-topics, (2) The number of face-to-face hours provided in the syllabus is not in accordance with the number of face-to-face hours curriculum provisions, in the curriculum there are 18 sub-topics with a total time of 36 hours face to face. While in the course of Monetary Economics with 15 sub-topics with a full time of 14 hours face to face.